Acid-functionalized nanoparticles for hydrolysis of lignocellulosic feedstocks - Peña Duque, Leidy E. (Kansas State University, 2009)
Acid catalysts have been successfully used for pretreatment of cellulosic biomass to improve sugar recovery and its later conversion to ethanol. However, use of acid requires a considerable equipment investment as well as disposal of residues. Acid-functionalized nanoparticles were synthesized for pretreatment and hydrolysis of lignocellulosic biomass to increase conversion efficiency at mild conditions. Advantages of using acid-functionalized metal nanoparticles are not only the acidic properties to catalyze hydrolysis and being small enough to penetrate into the lignocellulosic structure, but also being easily separable from hydrolysis residues by using a strong magnetic field. Cobalt spinel ferrite magnetic nanoparticles were synthesized using a microemulsion method and then covered with a layer of silica to protect them from oxidation. The silanol groups of the silica serve as the support of the sulfonic acid groups that were later attached to the surface of the nanoparticles. TEM images and FTIR methods were used to characterize the properties of acid-functionalized nanoparticles in terms of nanoparticle size, presence of sulfonic acid functional groups, and pH as an indicator of acid sites present. Citric acid-functionalized magnetite nanoparticles were also synthesized and evaluated. Wheat straw and wood fiber samples were treated with the acid supported nanoparticles at 80°C for 24 h to hydrolyze their hemicellulose fraction to sugars. Further hydrolysis of the liquid fraction was carried out to account for the amount of total solubilized sugars. HPLC was used to determine the total amount of sugars obtained in the aqueous solution. The perfluroalkyl-sulfonic acid functional groups from the magnetic nanoparticles yielded significantly higher amounts of oligosaccharides from wood and wheat straw samples than the alkyl-sulfonic acid functional groups did. More stable fluorosulfonic acid functionalized nanoparticles can potentially work as an effective heterogeneous catalyst for pretreatment of lignocellulosic materials.
Keywords: Acid-functionalized magnetic nanoparticles; Lignocellulosic biomass; Hydrolysis of cellulose; Energy (0791); Engineering, General (0537)